His death-mask with a dedication: 'Frau van Scheltema in Verehrung u. Freundschaft, Clara Ragaz' - Meiner, ...
His death-mask with a dedication: 'Frau van Scheltema in Verehrung u. Freundschaft, Clara Ragaz'.